7T OVERVIEW OF PREGNANT WOMEN IN THE WORK AREA DISTRICT 31 BPM KLATEN - Renny Ayu Saputri; Triwik Sri Mulati; Sri Redjeki (STIKES DUTAGAMA KLATEN, 2013)
The maternal mortality rate is very high, as evidenced WHO (world health organization) estimates that more than 585,000 women die during pregnancy and childbirth. Antenatal care in execution, in the minimal standard known 7T, which consists of: weight scales, blood pressure measurement, height measuring fundus, complete TT immunization, provision of iron tablets test against sexually transmitted diseases. Based on the results of preliminary studies that have been done, 5 midwives in independent practice through observation showed that the standard of service delivery 7T ANC is 5 midwives practice independently of standard services performed 7T weight scales, blood pressure measurement, height measuring fundus, tetanus immunization toxoid, giving iron tablets and colloquium, which was not done is a sexually transmitted disease tests, because they still lack equipment available in each - each BPM so in service standards ANC 7T 5 independent midwives has been implementing service standards 7T.